A political theology of nature - Scott, Peter, 1961- (Cambridge studies in Christian doctrine, 2003)
Peter Scott contends that current ecological problems must be addressed within theology. Drawing insights from deep ecology, ecofeminism, and social and socialist ecologies, he proposes a common realm of God, nature and humanity, offering a theological rationale for an ecological democracy, founded on the ecological renewal secured by Christ's resurrection.